(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The causes of water scarcity include climate change, population growth, pollution of water bodies, and inefficient use of resources. The article highlights the importance of water in nature and the solution to the problem of water scarcity, the development of seawater desalination technologies, modern methods such as reverse osmosis, which make it possible to obtain fresh water from seawater, etc.